A key that opens every door? rationality under the principle of legality today. - Sekhethelo, Maile (My University, 2019)
In recent years the principle of rationality has attracted more judicial attention than any other principles under the principle of legality. The principle has expanded such that the scope of what constitutes the principle of rationality and the manner in which the courts apply and interpret the principle has developed significantly. As it shall become apparent in this paper, the courts have interpreted the principle of rationality to demand procedural fairness and the right to be given written reasons. To this end, there is a confusion as to the scope of what constitutes the principle of rationality. It has also been evident that the courts interpret the principle to mean whatever the courts want it to mean. It will also become apparent that rationality may be susceptible to manipulation. It would seem, however, that in most cases the principle has become a more preferred ground of review than any other principle and thus a key that opens all doors. The objective of this research report is to explore the principle of rationality under the principle of legality as developed in the South African courts and ultimately answers the question of whether the principle has become the key that opens all doors in cases of alleged abuse of public power. The report finds that rationality is not a key that opens all doors.
Submitted in partial fulfilment of the requirements for the degree of Master of Laws by coursework and research report at the University of the Witwatersrand, Johannesburg, 2019